2023
DOI: 10.1002/cam4.6455
|View full text |Cite
|
Sign up to set email alerts
|

Association of immune checkpoint inhibitors therapy with arterial thromboembolic events in cancer patients: A retrospective cohort study

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) have emerged as a standard treatment for various malignancies. However, research indicates blocking the immune checkpoint pathway may exacerbate atherosclerotic lesions.ObjectivesWe aimed to investigate whether ICI therapy increases the risk of arterial thromboembolic events (ATEs).MethodsA retrospective cohort study was conducted on patients with histologically confirmed cancer at our institution between 2018 and 2021, using the propensity score matching method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Newer cancer therapies, including immune checkpoint inhibitors (ICIs), also carry an increased risk of ATE. In a retrospective cohort study comparing patients who received ICI with a control cohort of patients who did not receive ICI, the ICI group had an RR of 2.01 for developing ATE, with the RR increasing to 1.41 at 1 year and 1.97 at 4 years [ 35 ].…”
Section: The Pathophysiology Of Cancer-associated Atementioning
confidence: 99%
“…Newer cancer therapies, including immune checkpoint inhibitors (ICIs), also carry an increased risk of ATE. In a retrospective cohort study comparing patients who received ICI with a control cohort of patients who did not receive ICI, the ICI group had an RR of 2.01 for developing ATE, with the RR increasing to 1.41 at 1 year and 1.97 at 4 years [ 35 ].…”
Section: The Pathophysiology Of Cancer-associated Atementioning
confidence: 99%
“…A recent study [ 81 ] showed that patients treated with ICIs had a two-fold higher atherothrombotic (ATE) risk compared to controls (RR, 2.01 [95% CI (1.61–2.51)]; p < 0.001). The subgroup analysis revealed no significant increase in ATE risk for ICI-treated patients within 1 year, whereas the ATE risk rose by 41% at 1 year ( p = 0.010) and 97% at 4 years ( p ≤ 0.001) in the ICI group.…”
Section: Icis Therapy and Atherosclerotic Cardiovascular Disease: Cli...mentioning
confidence: 99%